PENGARUH KEBIASAAN BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK KELAS IV DI SDS ISLAM TERPADU SULTHONIYAH SAMBAS TAHUN PELAJARAN 2022-2023 - Yunida (Lunggi Journal, 2024)
This research discusses the Influence of Study Habits and Learning Motivation on Student Learning Outcomes in Class IV Thematic Learning at the Sulthoniyah Sambas Integrated Islamic SDS for the 2022-2023 Academic Year. The aim of this research is to reveal: 1) The influence of study habits on student learning outcomes in grade IV Thematic Learning at the Sulthoniyah Sambas Integrated Islamic SDS for the 2022-2023 academic year. 2) The influence of learning motivation on student learning outcomes in class IV Thematic Learning at the Sulthoniyah Sambas Integrated Islamic SDS for the 2022-2023 academic year. 3) the influence of study habits and learning motivation on student learning outcomes in class IV Thematic Learning at the Sulthoniyah Sambas Integrated Islamic SDS for the 2022-2023 academic year. This research uses a quantitative approach and associative research type. Data collection techniques use indirect communication and documentation techniques. The data analysis techniques used are simple linear regression and multiple linear regression. The research results show that: There is a significant influence between study habits and learning outcomes. Based on the results of correlation analysis, the R value is 0.703. This value is in the correlation coefficient interval of 0.600 -0.799, so this shows that there is a strong influence between study habits on student learning outcomes in class IV Thematic Learning at the Sulthoniyah Sambas Integrated Islamic SDS for the 2022-2023 academic year, namely 73.4%. There is a significant influence between learning motivation and learning outcomes. Based on the results of correlation analysis, the R value is 0.267. This value is in the correlation coefficient interval of 0.200 -0.399, so this shows that there is a low influence between study habits on student learning outcomes in class IV Thematic Learning at the Sulthoniyah Sambas Integrated Islamic SDS for the 2022-2023 academic year, namely 26.7%. There is a significant influence between study habits and study motivation. Based on the results of the correlation analysis, the R value is 0.703. This shows that this value is in the correlation coefficient interval of 0.600 - 0.799, so this shows that there is a strong influence between study habits on student learning outcomes in class IV Thematic Learning at Sulthoniyah Sambas Integrated Islamic School in 2018. Lesson 2022-2023 is 70.3%.